Proliferative capacity of murine hematopoietic stem cells. - Hellman, S (1978)
The present study demonstrates a decrease in self-renewal capacity with serial transfer of murine hematopoietic stem cells. Production of differentiated cell progeny is maintained longer than stem cell self-renewal. In normal animals the capacity for self-renewal is not decreased with increasing donor age. The stem cell compartment in normal animals, both young and old, appears to be proliferative quiescent. After apparent recovery from the alkylating agent busulfan, the probability of stem cell self-renewal is decreased, there is a permanent defect in the capacity of the bone marrow for serial transplantation, and the stem cells are proliferatively active. These findings support a model of the hematopoietic stem cell compartment as a continuum of cells with decreasing capacities for self-renewal, increasing likelihood for differentiation, and increasing proliferative activity. Cell progress in the continuum in one direction and such progression is not reversible.